Ivan Lanin's Instagram Account as a Medium for Learning Indonesian - Mulyana, Ajeng Tina; Syafaat, Saat; Fauziah, Amalia Kholisah; Lestariningsih, Dwi Kristina; Tauba, Zahrah Rahmadina; Rosmaldi, Rezka Rachima; Shafwan, Achmad (LPPM Universitas Mohammad Husni Thamrin, 2025)
Based on the researcher's observations in class IV of SDN 05 Kebon Pala, there were problems in learning Indonesian on the Enhanced Spelling material, as seen from the results of routine assessments that did not improve and there were difficulties for students in applying the correct EYD in making sentences and paragraphs. Enhanced Spelling (EYD) as a guideline for Indonesian spelling is a very important strategic step in strengthening the identity of the Indonesian language and culture. Consistency in the use of spelling will facilitate communication, increase international competitiveness, and strengthen the cultural identity of Alwi, Lapoliwa, and Moeliono. To overcome this, the researcher conducted classroom action research. From the results of the study, it can be concluded that the use of learning videos from Instagram accounts, especially from the @ivanlanin account, has a positive effect on the learning outcomes of Indonesian on the EYD material of class IV of SDN 05 Kebon Pala. Students find it easier to understand the material because it uses attractive visual displays, the explanations are short, clear, and use language that they know every day. In addition, because the media comes from a platform that is familiar to them, students feel closer and do not feel like they are studying boringly. This result is also in accordance with the theory that states that interesting and relevant learning media to the world of students can increase their interest in learning and learning outcomes. Social media such as Instagram is not only for entertainment, but can be used for positive things such as learning.